Risk and protective factors for the psychological well-being of children orphaned by AIDS in Cape Town, South Africa - Cluver, L; Lucie Cluver (2007)
Background: Orphanhood is a major consequence of the HIV/AIDS epidemic in sub-Saharan Africa. There is little evidence concerning psychological problems for AIDS-orphaned children. This thesis explores the relationship between orphanhood status and mental health. It also examines mediating influences of environmental risk and protective factors, and interactions between factors, on children’s psychological problems. Methods: 1200 isiXhosa-speaking children were interviewed, using standardised questionnaires, in deprived urban settlements of Cape Town. A qualitative stage with 60 AIDS-orphaned children, 42 caregivers and 20 professionals explored participant perceptions of risk and protective factors. A quantitative stage compared 1025 AIDS-orphaned children to control groups of other-orphans and non-orphans. Data were analysed with t-tests, chi-sq, anovas, regression and log-linear analyses. The study took place in collaboration with Cape Town Child Welfare. Results: AIDS-orphaned children reported more depression (p<.001), peer relationship problems (p<.001), post-traumatic stress (p<.001), suicidal ideation (p<.05), delinquency (p<.001) and conduct problems (p<.001) than other-orphans and non-orphans. Anxiety showed no differences. Compared to Western norms, AIDS-orphaned children showed higher levels of internalising problems and delinquency, but lower levels of conduct problems. These differences remained when controlling for socio-demographic factors. A number of factors strongly mediated the relationship between AIDS-orphanhood and mental health. These include poverty-related factors (food, education and social security, p<.001). caregiving-related factors (caregiver illness, p<.001, excessive housework p<.001, being a streetchild, p<.001) and AIDS-related stigma (p<.001). Cumulative effects were also found. Food insecurity and AIDS-related stigma interacted to raise likelihood of disorder from 19% to 83%, and orphanhood status and bullying interacted to raise likelihood from 12% to 76%. Conclusions: This thesis shows clear evidence of heightened psychological problems amongst AIDS-orphaned children. It also indicates mediating factors and points to areas of possible intervention. The South African Ministry of Social Development plans to scale up the study to a national survey of AIDS-orphanhood.